GE_GERICHTE A/3653/2024 vom 7. November 2024 - GE Cour de justice (2024)
DÉTENTION AUX FINS D'EXPULSION;MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);LÉGALITÉ;ADÉQUATION;PROCÉDURE ÉCRITE | LEI.76a.al1; LEI.76a.al2; LEI.80a.al3; Règlement Dublin III.28.ch2